MODEL PENDIDIKAN KETELADANAN KEPEMIMPINAN: TANTANGAN PENGEMBANGAN SUMBER DAYA MANUSIA - Render Bin Luwis (Sekolah Tinggi Teologi Excelsius, 2020)
Abstract:Â Theoretical basis: Education (pedagogy) means science that investigates, and reflects on, the symptoms of educating. Research Objectives: To answer the following questions: (1) What is meant by exemplary leadership education? (2) How is exemplary education in teaching unity with the church based as a role model in resource development? (3) What is the model for exemplary leadership education? Methods: The research method in this article is qualitative, while the data collection techniques use interviews and observations, while the data collection technique has a data analysis process using the Husserlin phenomenology approach. Results: (1) Leadership education based on Ephesians 4: 1-16 is a model of exemplary character, exemplary teaching in church unity, and exemplary in church maturity. (2) Exemplary education in teaching unity with the congregation is based as a role model in human resource development among God's servants in GBBM that can be emulated by the congregation is an example of the character of Jesus Christ who is the only Lord and Savior for all people, ) The leadership model of